Secagem por atomização do extrato de sapota-do-solimões (Matisia cordata) - Silva, Carlos Ramon de Paula (2021)
The sapota-do-solimões is a native fruit of the Amazon region and has a high content of phenolic compounds and carotenoids. This fruit has a high moisture content and, consequently, is highly perishable. Therefore, its bioactive compounds are very unstable to processing and storage, as they are sensitive to factors such as humidity, temperature, light and oxygen. The stability of these fruits and their bioactive compounds can be increased by spray drying, using carrier agents. Therefore, the sapota-do-solimões powder extracts obtained by spray drying were evaluated for physicochemical and morphological properties, and stability of volatile compounds, using the following combinations of carrier agents: T1 = maltodextrin (MD) with DE 5 and inulin (IN); T2 = MD with DE 10 and inulin (IN); T3 = MD with DE 20 and inulin (IN). In general, moisture and water activity values ranged from 3,35-3,76 (g water.100g-1 b.s.) and 0,38-0,39, respectively. The retention of volatile compounds was low. Regarding morphology, the particles were spherical in shape with a smooth and pore-free surface. However, there was agglomeration of particles. Treatments T2 and T3 showed greater hygroscopicity and treatment T1 showed lower water adsorption capacity. Regarding the stability of the powders, the increase in equivalent dextrose was a factor that affected all treatments in relation to thermal degradation and stability of volatile compounds. The T3 treatment showed more satisfactory results in relation to the stability of volatile compounds in the powders.